The Dnipro Left Bank Forest-Steppe Region in the Hunnic Period - Roman M. Reida; Anatoliy V. Heiko; Sapiehin V. Sergiy (Archaeologia Polona, 2024)
The article deals with the ethno-cultural situation in the Dnipro Left Bank Forest-Steppe region during the Hunnic period based on a consideration of material from the sites discovered in this region, primarily burial sites, that contain finds from the last quarter of the 4th – the first half of the 5th century B.C. The sites were divided into three groups: 1) burials of nomads with some elements of Cherniakhiv culture; 2) “syncretic” burials of the Cherniakhiv culture with nomadic elements; 3) sites of Cherniakhiv culture. The existence of these sites is caused by contacts between the nomadic world and the Cherniakhiv population, who may be classified as farmers. These active contacts demonstrate different degrees of incorporation of nomads into the Cherniakhiv environment. The description of the burials that belong to these groups is presented in the article. Among them, burial 124 of the Shyshaky cemetery can be mentioned here. Due to the size of the grave and individual finds, this burial complex stands out among the sites of the Cherniakhiv culture and should be classified as belonging to the burials of princes. Based on archaeological finds, it can be stated that the arrival of the Huns did not cause catastrophic consequences for the population of the Dnipro Left Bank Forest-Steppe region. At that time, it was not a decline, but a development of the culture of the nomads (the Alans) and also the settled population of the Cherniakhiv culture.